Proof-of-Concept Study of Multifunctional Hybrid Nanoparticle System Combined with NIR Laser Irradiation for the Treatment of Melanoma - Lopes, Joana (2022)
Supplementary Materials - available online at https://www.mdpi.com/article/10.3390/biom11040511/s1